Nature interpretation as the scene for a deliberative process and a medium for commoning? - Egeløv Haugen, Nanna (2015)
Sustainability has been the global answer when looking towards solving pressing environmental problems. We need to create sustainability to ensure good living conditions for present and future generations. However the institutionalization of the environmental question has created a dominating environmental discourse unable to create solutions within the contemporary democratic frame. Nature interpretation has in this study been looked at as a potential institution for creating a deliberative space and a mediator for a process of commoning concerning the question of sustainability. Nature interpretations current approach towards the question of sustainability, as well as the institutions role within the contemporary democratic frame, has been analyzed. Five semi-structured interviews and four participatory observations have been conducted and from, together with a literature review, the base on which the analysis have been made. This study showed that the question of sustainability is included in nature interpretation activities at a very limited level and is based on a practical approach of how everyday life activities can become more sustainable. The approach of creating a deliberative space and mediating a process of commoning has not been pursued. The capacities of nature interpretation as an institution has developed within the capacities of current society and is therefore constituted by the barriers within society in regards to creating new capacities and enable a discussion of the values and ethics concerning sustainability. It has therefore shown that the structures within the contemporary democratic frame constitute the challenge of including the question of sustainability in nature interpretation activities, more so than the barriers connected to the practical approach of doing so.